Abandoning wealth for scarcity": a critical discourse of youth's orientation of rural-urban migration in Southwestern Nigeria (2024)
This study critically examined the underlying factors driving this migration trend and its socio-economic implications. The study adopted mixed methods research design. Population comprised all youths in Southwestern Nigeria. The multi-stage sampling procedure was adopted. From each of the state simple random sampling was used to select three Local Government Areas (LGAs) each. Purposive sampling technique was used to select 35 participants from each of the LGAs making a total of 315 participants. The participants were purposively selected based on some criteria which are - he/she must have migrated to current location, must be within the age range of 30 and 49 years old; must be willing to participate in the study. In-depth interviews were conducted with key participants (two per LGA). Data collected were analysed using descriptive statistics and thematic analysis. Findings showed that youths have positive orientation towards rural-urban migration and are not aware of potentials in rural areas; the Lack of infrastructure development in rural areas, lack of, support system and healthcare were rated as factors predisposing rural urban migration. It is also discovered that there was persistent decline in the population of the host communities, even the available ones comprise of aged men and women, people are running away from farming. Results show various plausible solutions however, recommended that youths need to explore rural wealth with modern technological approach. There is need for critical investments in rural community for multiple wealth creation and development.